Efficacy of Losartan within a Multicomponent Secondary Prevention Strategy for Cardiovascular Events in Post-Ischemic Stroke Patients - Halich, Viktoriya-Svitlana M.; Kobyliak, Nazarii M.; Pletenetska, Alina O. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Aim. To assess the efficacy of adding losartan to standard therapy in patients with ischemic heart disease (IHD) and polyvascular atherosclerosis following ischemic stroke as part of a multicomponent secondary prevention strategy over a 4-month treatment period. Materials and Methods. A prospective study enrolled 60 patients who were randomly assigned to two equal groups: standard therapy (including antiplatelet agents, statins, antihypertensive medications, and risk factor management) and standard therapy plus losartan. All patients underwent assessment of lipid profiles, as well as serum levels of the matrix metalloproteinases MMP-2 and MMP-9, interleukin-1β (IL-1β), plasminogen activator inhibitor-1 (PAI-1), thrombin-activatable fibrinolysis inhibitor (TAFI), and tumor necrosis factor-alpha (TNF-α), both at baseline and after 4 months of therapy. Results. After 4 months of therapy, a significant reduction in the serum levels of lipids (TC, TG, LDL-C, HDL-C), MMP-2, MMP-9, IL-1β, PAI-1, TAFI, and TNF-α (p<0.05) was observed in both groups. However, compared with the standard therapy group, the addition of losartan was associated with a significant reduction in MMP-2 (p = 0.008) and TAFI (p = 0.011) in the intergroup ANCOVA analysis. Conclusions. The addition of losartan to standard therapy in patients with IHD and polyvascular atherosclerosis following ischemic stroke over a 4-month period was associated with improved clinical outcomes, attenuation of inflammatory and proteolytic cascade activation, and enhanced hemodynamic parameters.